Clinical Safety Experience of TAK-003 for Dengue Fever: A New Tetravalent Live Attenuated Vaccine Candidate. (26th May 2022) - Patel, Sanjay S; Rauscher, Martina; Kudela, Maria; Pang, Hang
Abstract: Background: An unmet medical need remains for an effective dengue tetravalent vaccine that can be administered irrespective of previous dengue exposure. TAK-003, a dengue tetravalent vaccine, has demonstrated efficacy in an ongoing phase 3 trial in children and adolescents living in dengue-endemic areas, with an acceptable safety profile in both dengue-naive and dengue-exposed individuals. Methods: Safety findings are presented herein from an integrated analysis of data for healthy 4–60-year-olds from two phase 2 and three phase 3 double-blind, placebo-controlled clinical trials of TAK-003 (TAK-003, n = 14 627; placebo, n = 7167). Safety evaluation included analyses of postinjection reactogenicity, unsolicited adverse events (AEs), serious AEs (SAEs), and deaths. Subgroup analyses were performed by age group, baseline serostatus, and gender. Results: The most common local and systemic AEs were injection site pain (43% for TAK-003 and 26% for placebo) and headache (34% and 30%, respectively). Injection site AEs were mostly mild and resolved within 1–3 days. Unsolicited AEs and AEs leading to discontinuation occurred with similar frequency across both groups, while SAEs were fewer for TAK-003 recipients (6% vs 8% for placebo). Four of the 5 vaccine-related SAEs (which included hypersensitivity, dengue fever, and dengue hemorrhagic fever) occurred in the placebo group. No deaths were considered vaccine-related. Subgroup analyses showed no differences in safety by baseline serostatus or by gender, albeit analysis by age indicated greater local reactogenicity rates for adolescents (46% for TAK-003 and 28% for placebo) and adults (56% and 19%, respectively) than for children (37% and 25%, respectively). Conclusions: No important safety risks were identified, and TAK-003 was well tolerated irrespective of age, gender, or baseline dengue serostatus in recipients aged 4–60 years. Abstract : In this integrated safety analysis of 5 phase 2 and 3 double-blind, randomized, placebo-controlled trials in 4–60-year-olds, TAK-003, a dengue tetravalent vaccine, was well tolerated irrespective of age, sex, or baseline dengue serostatus, with no important safety risks identified.